2022
DOI: 10.3390/earth3030049
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemicals and Shade Complexity Affect Soil Quality in Coffee Home Gardens

Abstract: Soil quality can directly influence the health, yield, and quality of a particular crop species, and agrochemicals are often used to boost soil micro- and macro-nutrients. The excessive application of agrochemicals, however, is often the cause of imbalances in acidity and nutrient concentration and can cause soil to deteriorate. The presence of multiple shade trees in farmland can positively influence soil quality. Here, we evaluate the effect of agrochemical use (i.e., organic, mixed, and intensive) and shade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Akpalu et al [29] recommended that it would be financially reasonable to combine an inorganic P source with the organic material in the management of F. albida parklands in Ghana because the tree leaf biomass typically contains a higher N/P ratio than that required by the crops, while the P may become deficient in an attempt to supply N via F. albida leaf litter application. Manson et al [56] found lower pH levels in coffee farms using agrochemicals and farms dominated by Eucalyptus trees in West Java. Thus, planting native fruit tree species rather than eucalyptus trees as shade trees for coffee plants with the application of organic manure or liming is recommended.…”
Section: Nutrient Management and Fertilizer Applicationmentioning
confidence: 99%
“…Akpalu et al [29] recommended that it would be financially reasonable to combine an inorganic P source with the organic material in the management of F. albida parklands in Ghana because the tree leaf biomass typically contains a higher N/P ratio than that required by the crops, while the P may become deficient in an attempt to supply N via F. albida leaf litter application. Manson et al [56] found lower pH levels in coffee farms using agrochemicals and farms dominated by Eucalyptus trees in West Java. Thus, planting native fruit tree species rather than eucalyptus trees as shade trees for coffee plants with the application of organic manure or liming is recommended.…”
Section: Nutrient Management and Fertilizer Applicationmentioning
confidence: 99%
“…Pessaraki and Szabolcs [20] also reported that the organic matter addition reduces the soil pH. Trees have the capacity to moderate the effects of leaching by way of contribution of bases to the soil [21].…”
Section: Phmentioning
confidence: 95%